The Effect of School Transparency and Principal Competence on the Effectiveness of Budget Management in Elementary Schools in Bandung Regency - Lamatokan, Sisca Cletus; Syamsurizal, Syamsurizal; Sopiah, Sopiah; Meliana, Meliana (Westscience Press, 2024)
This study investigates the effect of school transparency and principal competence on the effectiveness of budget management in elementary schools in Bandung Regency. A quantitative approach was employed, involving 65 respondents from selected schools. Data were collected using a structured questionnaire and analyzed using SPSS version 25. The findings revealed that both school transparency and principal competence positively and significantly influence budget management effectiveness. Furthermore, these two factors jointly explain 67% of the variance in budget management effectiveness. The results highlight the critical role of transparent practices and leadership competence in optimizing financial resource management in educational institutions. The study recommends enhancing transparency mechanisms and providing targeted leadership training for school principals to improve budget management outcomes.